2020
DOI: 10.1111/1477-8947.12209
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustainable development goals through participatory forest management: Examples from South‐Eastern Bangladesh

Abstract: Forests managed through peoples' participation can help to achieve a number of sustainable development goals (SDGs). This paper, drawing data from four participatory forest management (PFM) projects in south‐eastern Bangladesh, explored: (a) the factors that influenced the outcomes of PFM; and (b) contribution of PFM towards achieving selected SDGs. The research used observation, semi‐structured household interviews, group discussions, vegetation survey and Ostromʼs design principles for data collection, Diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…3). This observation agreed with the findings of Hammond et al 42 , Aigbe and Omokhua 43 , Aigbe et al 44 , Adeyemi et al 11 , Salami and Akinyele 45 , and Burju et al 46 47 reported that timber trees are logged at 60-90 cm DBH depending on the species. Similar results have been reported by the International Institute of Tropical Agriculture (IITA) Ibadan, Oyo state and on tree species composition in selected sacred forests in Nigeria by Christopher 48 and Daniel et al 49 .…”
Section: Results Of Frequency Class Distribution Of Plant Species Insupporting
confidence: 91%
“…3). This observation agreed with the findings of Hammond et al 42 , Aigbe and Omokhua 43 , Aigbe et al 44 , Adeyemi et al 11 , Salami and Akinyele 45 , and Burju et al 46 47 reported that timber trees are logged at 60-90 cm DBH depending on the species. Similar results have been reported by the International Institute of Tropical Agriculture (IITA) Ibadan, Oyo state and on tree species composition in selected sacred forests in Nigeria by Christopher 48 and Daniel et al 49 .…”
Section: Results Of Frequency Class Distribution Of Plant Species Insupporting
confidence: 91%
“…Restoration of native flora by planting native species in mixed species plantations while facilitating agroforestry supports the findings of earlier studies (e.g. Budiharta et al 2014;Brancalion & Chazdon 2017;Nath et al 2020), where agroforestry is recommended for ecosystem restoration and conservation of genetic diversity. In highly degraded landscapes, forest land restoration can improve ecological functionality and agricultural productivity (César et al 2021) by limiting pressure on the remnant natural forests and augmenting landscape connectivity with nearby forests.…”
Section: Ecological Aspects Of the Studied Cbfr Projectssupporting
confidence: 84%
“…Since the 1970s, the government of Bangladesh has undertaken a number of research and development projects aimed at restoring forests through community participation. The Betagi-Pomra agroforestry project (1979) and the community forestry project (1981) in the country's south-eastern and northern regions, respectively, are the two most notable (Khan 2016;Nath et al 2016aNath et al , 2020. Based on promising results, the trend has since continued in the forms of social forestry (1980s to the end of the 1990s), comanagement of protected areas (since 2004), and contemporary collaborative forest management (Nath et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the energy sector, various renewable energy sources are used and studied to ensure sustainable energy production and distribution in Bangladesh [66][67][68][69]. In the forestry sector, several studies are conducted to uphold SGDs in Bangladesh [70][71][72][73]. Islam et al [74] and Islam and Shamsuddoha [53] studied marine fisheries in Bangladesh with a view of sustainable conservation and management of coastal and marine fisheries industries.…”
Section: Status Of Sustainable Development Goals Initiatives In Bangladeshmentioning
confidence: 99%